Risk of herpes zoster in patients prescribed inhaled corticosteroids: a cohort study - Ernst, Pierre (BioMed Central, 2011)
BACKGROUND: Little is known concerning risk factors for herpes zoster in the general population. We hypothesised that inhaled corticosteroids (ICS) are a risk factor for herpes zoster especially among users of inhibitors of cytochrome P450 enzymes involved in their metabolism. METHODS: We identified a cohort of adult users of respiratory medications in the General Practice Research Database and carried out a nested case control analysis of inhaled corticosteroid use among 8900 new cases of herpes zoster and 88032 controls matching on age and calendar time. RESULTS: The adjusted odds ratio for the relationship between current use of ICS and the occurrence of herpes zoster was 1.00 (95% confidence interval (CI), 0.94-1.07). There was no increase in risk of herpes zoster even at higher ICS doses; odds ratio 1.05 (95% CI, 0.96-1.14). Among subjects with concomitant prescriptions for an ICS and an inhibitor of cytochrome P450 3A4, the point estimate for the association between herpes zoster and the use of higher doses of inhaled corticosteroids was 1.23 (95% CI, 0.81-1.88). CONCLUSIONS: The use of inhaled corticosteroids, even at high doses and in conjunction with inhibitors of their metabolism, was not a significant risk factor for the occurrence of herpes zoster in adults.